2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23490
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Pedagogies Promoting the Art of Structural and Civil Engineering

Abstract: IntroductionStudents who switch out of STEM majors frequently cite uninspiring introductory lecture courses 1 and poor teaching 2 as among the reasons for this decision. An active learning approach to teaching (i.e. one that emphasizes learning by doing) has been shown to improve student performance and retention in STEM 2,3 , as well as increase student motivation and interest 1,4 . Students taught using active learning remember more, and are better able to apply their knowledge [5][6][7][8] . Furthermore, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous conference papers by the authors have illustrated some examples of effective teaching approaches. For example, [7] discusses some kinesthetic activities, [8] discusses effective practices using online polling, and [9] discusses effective interactive methods for teaching reinforced concrete. This paper specifically focuses on interactive lecture demonstrations (not just 'plain' lecture demonstrations).…”
Section: Overview Of Structures Course and Interactive Teaching Methodsmentioning
confidence: 99%
“…Previous conference papers by the authors have illustrated some examples of effective teaching approaches. For example, [7] discusses some kinesthetic activities, [8] discusses effective practices using online polling, and [9] discusses effective interactive methods for teaching reinforced concrete. This paper specifically focuses on interactive lecture demonstrations (not just 'plain' lecture demonstrations).…”
Section: Overview Of Structures Course and Interactive Teaching Methodsmentioning
confidence: 99%
“…For compositions of PBL, the classroom roles shift from teacher focused to student-centered learning models that more self-directed [20]. In both cases, studies have shown that PBL has led to improved student performance, higher quality of peer interactions, and more positive student attitudes [6].…”
Section: Support For Project Adoptionmentioning
confidence: 99%
“…In the rapidly advancing built environment there is an emergent need for structural engineering students to know even more about design and other fields that they will work with [5]. There is increasingly higher demand for engineers who have these skills that go well beyond the technical knowledge gained through a typical engineering curriculum [6]. Civil Engineering, Architectural Engineering, and Construction Management programs are under pressure by industry to add content into the curriculum that address the changing nature of the engineering marketplace [1].…”
Section: Introductionmentioning
confidence: 99%